Respostas

2013-11-17T09:32:22-02:00
A) 4x+12-6x=7-3x-2
4x-6x+3x = 7 -2 -12
x=-7

b) 3x+6+2x=1+4x+8
3x+2x -4x=1+8-6
x=3

c)  5y+2-y=6+y+5
5y-y=5+6-2
4y= 9
y=9/4

d)  7x-14+3x=2+6x+8
7x+3x-6x=+8+2 +14
4x=24
x=24/4
x=6

e)  x+6-2x=x+5-2x
x-2x-x+2x=5-6
-2x=-1  (-1) multiplica para o x ficar positivo)
2x=1
x= 1/2  ou 0,5

f)  8+15x+5=8x-7-3x
15x-8x+3x=-8-5-7
10x=-20
x= -20/10
x= -2

g)  2x+6+3x=18-2x
2x+3x +2x= 18 -6
7x=12
x=12/7

h)  x-5+5x=4+3x+21
x+5x -3x=+21+4 +5
3x=30
x= 30/3
x=10

i)  2x-4+12x=15x+8
2x+12x -15x=+8 +4
-x=12   (-1) multiplica para o x ficar positivo)
x= -12

j)  5-2x+6=x+1-2x
-2x - x +2x= 1-6 -5
-x =-10   (-1) multiplica para o x ficar positivo)
x= -10

k)  x-2+2x=7+3x+6
x+2x-3x=+6+7+2
0x= +15
x=15/0  todo nº dividido por 0 é igual a 0
x=0
1 5 1